Serum levels of EphA2 are elevated in knee osteoarthritis and associated with disease severity - Xiao, Maping; Ji, Lei; Feng, Shuang; Qian, Wenbin (Frontiers in Medicine, 2025)
BackgroundThis study investigated the clinical relevance of serum ephrin type-A receptor 2 (EphA2) in patients with knee osteoarthritis (OA) compared to healthy controls and its association with disease severity, inflammatory markers, oxidative stress, and cartilage metabolism.MethodsA total of 258 participants, including 138 patients with primary knee OA and 120 age- and sex-matched healthy controls, were recruited between January 2023 and December 2024. OA severity was assessed using the Kellgren-Lawrence grading system, and clinical symptoms were assessed using the WOMAC score. Statistical analyses included group comparisons, Pearson correlations with Benjamini-Hochberg FDR adjustment, ROC curves for diagnostic performance, and multivariate logistic regression to identify independent risk factors.ResultsAmong patients with knee OA, those with Kellgren-Lawrence (K-L) grade III–IV had significantly higher EphA2 levels than those with K-L grades I–II. Receiver operating characteristic (ROC) analysis determined an optimal EphA2 cut-off of 276.8 pg./mL, yielding 92% sensitivity, 72% specificity, and an AUC of 0.924. After false discovery rate (FDR) correction, EphA2 remained positively correlated with the WOMAC score (r = 0.363, q < 0.003), ESR (r = 0.251, q < 0.006), TNF-α (r = 0.213, q < 0.012), MDA (r = 0.238, q < 0.009), COMP (r = 0.208, q < 0.018), MMP-13 (r = 0.200, q < 0.021), IL-6 (r = 0.198, q < 0.024), and ACSL4 (r = 0.200, q < 0.021). Consistently, serum EphA2 levels showed strong associations with cartilage degradation markers (COMP, HA, MMP-13, and CTX-2), inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-17A), oxidative stress (MDA), and ferroptosis (ACSL4), while displaying negative correlations with cartilage synthesis markers (PIICP and aggrecan) and antioxidant defenses (GSH and GPX4). Multivariate logistic regression further identified EphA2 (OR = 1.019, 95% CI: 1.009–1.029, p < 0.001), WOMAC, and TNF-α as independent risk factors for poor prognosis in knee OA.ConclusionThese findings suggest that EphA2 is closely associated with cartilage degradation, inflammation, oxidative stress, and ferroptosis in knee OA and may serve as a promising biomarker for disease diagnosis and progression monitoring.